2005
DOI: 10.1111/j.1471-0528.2005.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Antral follicle count, anti‐mullerian hormone and inhibin B: predictors of ovarian response in assisted reproductive technology?

Abstract: Objective The objective of this study was to evaluate the relationship between anti-mullerian hormone (AMH), inhibin B and antral follicle count (AFC) with ovarian response. Design Retrospective study. Setting Fertility unit.Sample AFC was recorded, and a serum sample obtained on day 3 from all patients undergoing in vitro fertilisation (IVF). Patients were given 300 IU/L recombinant follicle stimulating hormone (FSH; Gonal F).The following day blood samples were collected. Methods Serum samples were assayed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
2
25

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(206 citation statements)
references
References 33 publications
(25 reference statements)
11
168
2
25
Order By: Relevance
“…In our study, estrodiol levels on the day of HCG administration and the number of retrieved oocytes showed a gradual increase from the low to high AMH group, but the total dose of gonadotrophins was significantly decreased. Our report is in agreement with previous studies indicating that serum AMH levels on day 3 of the stimulation cycle positively predict ovarian responsiveness to gonadotrophins [18,19]. But the result may seem paradoxical given that an inhibitory effect of AMH on FSH-stimulated aromatase mRNA expression has been shown in human granulosaluteal cell [20], suggesting the remarkably increased AMH may reduce follicle sensitivity to FSH and estradiol production.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, estrodiol levels on the day of HCG administration and the number of retrieved oocytes showed a gradual increase from the low to high AMH group, but the total dose of gonadotrophins was significantly decreased. Our report is in agreement with previous studies indicating that serum AMH levels on day 3 of the stimulation cycle positively predict ovarian responsiveness to gonadotrophins [18,19]. But the result may seem paradoxical given that an inhibitory effect of AMH on FSH-stimulated aromatase mRNA expression has been shown in human granulosaluteal cell [20], suggesting the remarkably increased AMH may reduce follicle sensitivity to FSH and estradiol production.…”
Section: Discussionsupporting
confidence: 92%
“…This large decline in AMH over a relatively short period of time was not accompanied by any significant change in antral follicle count, serum FSH or inhibin B levels, suggesting that AMH is the most sensitive maker of ovarian reserve [7]. Since then several reports have confirmed that serum AMH is the most sensitive predictor of ovarian response to COH compared to more traditional markers such as age, FSH, inhibin B, antral follicle count and ovary volume [8,9].…”
Section: Introductionmentioning
confidence: 80%
“…Firstly, serum AMH has been shown to be the most sensitive predictor of ovarian response to COH compared to serum FSH, inhibin B, oestradiol, antral follicle count and ovary volume [8,9]. Secondly, unlike serum FSH, inhibin B and oestradiol levels, serum AMH levels appear to be relatively stable throughout the menstrual cycle [29][30][31], making assessment of ovarian reserve possible at any stage of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, various sensitivities and specificities of the screening tests are reported. Table 1 ( 15,16,21,22,[26][27][28] compares a selected summary of screening tests commonly used to evaluate for ovarian response in ART with reported sensitivities and specificities. (29), as the threshold considered to be normal is increased, there is improvement in specificity, but a corresponding reduction in sensitivity.…”
Section: Screening For Ovarian Insufficiencymentioning
confidence: 99%